EZ PZ Company Duo Bedsheet / Nursyamila Mohd Noordin... [et al.] - Mohd Noordin, Nursyamila; Rahazi, Nurul Azrin; Rosani, Nur Iffah; Hamzah, Fatin Aina Aqilah; Norazlan, Nurul Izzaty (2020)
EZ PZ Company offers bedding product and service to customers. With three different sizes (single, queen & king) and varieties of patterns with vibrant colours of bed sheet, our product would also provide satisfaction to customer. Our product is innovated by combining bed sheet with blanket known as "Duo Bedsheet" which make it easier to tidy and time saving. Our clients are mainly targeted to middle class who want easily managed, neat and time-saving beddings. We also targeted on career person and students that required making up their bed after waking up in nick-of-time. Duo Bedsheet offers a satisfaction of organised and tidy beddings towards customers especially when they are back from work or classes, looking at their tidy bed will at least release their stress and have a omfortable sleeping experience with our product.